2023
DOI: 10.1021/acs.cgd.3c00060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polar Protic Solvents on Urea Morphology: A Combination of Experimental and Molecular Modeling

Abstract: The modification of crystal shapes is used intensively in designing particles with desired properties to ensure the efficiency of the manufacturing processes. In this work, urea crystals grew in various polar protic solvents by cooling crystallization that produced α-form urea. The aspect ratios of the crystals were found to be in the range from 14.77 to 1.44, grown in the following solvents: water > methanol > ethanol > isopentanol > isobutanol > pentanol > butanol > propanol > isopropanol. An attempt to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…10). 82,83 The polar (1 1 1) and (−1 −1 −1) faces are not equivalent and the two end caps of needles grown from methanol are twisted by 90 degrees. The reason for this is that the growth rate of steps on [1 1 0] in the + c direction is twice that in the − c direction, while it is the reverse for [1 −1 0] and [−1 1 0].…”
Section: Use Of Additives To Reduce the Aspect Ratio Of Needlesmentioning
confidence: 99%
“…10). 82,83 The polar (1 1 1) and (−1 −1 −1) faces are not equivalent and the two end caps of needles grown from methanol are twisted by 90 degrees. The reason for this is that the growth rate of steps on [1 1 0] in the + c direction is twice that in the − c direction, while it is the reverse for [1 −1 0] and [−1 1 0].…”
Section: Use Of Additives To Reduce the Aspect Ratio Of Needlesmentioning
confidence: 99%
“…For example, the effect of solvents that contains hydroxyl functional groups on paracetamol Form I crystal surfaces carried out using this technique has shown that the most favourable solvent binding on the {002} facet delayed the growth of an elongated hexagonal morphology along the c-axis, forming a prism-like morphology (Shahrir et al, 2022). In their other work, they reported the influence of polar protic solvents on urea crystal morphology, which resulted in {111} and {001} capping facets as the most negative binding energy and {110} as the lowest negative binding energy, hence affecting the overall crystal morphology from an elongated cuboid to a prismoidal shape (Shahrir et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors affecting the polymorphism of mefenamic acid are the choice of solvent, temperature, supersaturation, stirring, and the presence of interfaces or impurities during the crystallisation process (Abdul Mudalip et al, 2018). This work aims to investigate the nature of the solute-solvent interactions between mefenamic acid (Form II) and acetone or dimethylformamide (DMF) at the molecular level using the surface docking method as described by previous researchers (Shahrir et al, 2022;Shahrir et al, 2023). The method involves the docking of the solvent molecule on top of the crystal surfaces of interest, e.g., {001}, {010}, and {011} facets.…”
Section: Introductionmentioning
confidence: 99%
“…It plays a pivotal role in assessing product quality . The crystal habit is predominantly influenced by the molecular arrangement within the crystals and the external environment, , such as the solvent, , supersaturation, , temperature, template, and additives . The crystals’ habit significantly impacts the overall quality of the final product during industrial crystallization.…”
Section: Introductionmentioning
confidence: 99%